A Dimensional Approach to Discrepancy in Parenting Styles in Russian Families - Marina A. Zhukova; Nan Li; Vitalii Zhukov; Elena L. Grigorenko (MDPI AG, 2023)
We investigated the magnitude and direction of differences in parenting styles as they relate to children's mental health problems, as assessed using the CBCL. The sample consisted of 306 families residing in a large industrial city in Russia. We aimed to expand the cross-cultural literature on parenting styles by assessing a sample of Russian families and analyzing how agreement versus disagreement between self-reported and partner-reported parenting styles related to children's mental health problems. The findings suggested that both congruence and incongruence between parenting styles could be associated with children's mental health problems. When parents agreed about high warmth and matched on lower levels of demandingness, in line with the permissive parenting style, children tended to exhibit maladaptive behavior and externalizing problems. We also registered that children were likely to show low levels of mental health problems when fathers had higher self-reported warmth compared with mothers' reports. In contrast, children whose fathers had higher self-reported demandingness compared with the mothers' reports, exhibited moderate levels of mental health problems. This study expands the existing literature by providing a dimensional approach to children's mental health difficulties in the context of (dis)agreements in the parenting styles within a family.